2011
DOI: 10.1002/jccs.201190020
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Glycosides from the Leaves of Machilus philippinensis

Abstract: Thirteen flavonoid glycosides (1-7, 11-13, 15, 17, and 18) were isolated from the EtOH extract of the leaves of Machilus philippinensis. Of these, kaempferol (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…These results are consistent with the structure of units, which are all epicatechin with hydroxyl groups at C3′ and C4′. According to the evidence outlined above and a comparison of the ESI‐MS, 1 H‐NMR and 13 C‐NMR data with values in the literature, compound 2 was determined to be parameritannin A1 (epicatechin‐(2β → O7,4β → 8)‐[epicatechin‐(4β → 6)]‐epicatechin‐(4β → 8)‐epicatechin) (Fig. b).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These results are consistent with the structure of units, which are all epicatechin with hydroxyl groups at C3′ and C4′. According to the evidence outlined above and a comparison of the ESI‐MS, 1 H‐NMR and 13 C‐NMR data with values in the literature, compound 2 was determined to be parameritannin A1 (epicatechin‐(2β → O7,4β → 8)‐[epicatechin‐(4β → 6)]‐epicatechin‐(4β → 8)‐epicatechin) (Fig. b).…”
Section: Resultssupporting
confidence: 83%
“…The α‐glucosidase (EC 3.2.1.20) inhibitory assay was performed according to Lin and Lee . The α‐amylase (EC 3.2.1.1) inhibitory assay was carried out according to Apostolidis et al with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The 13 C NMR spectrum showed that procyanidins units are connected mostly by C4-C8 and C4-C6 interflavonoid bonds to B-type procyanidins: 36.2 ppm is for C4 in interflavonoid cis/trans link and a small signal at 29.8 ppm is for C4 in terminal units, 106.2 ppm (C8 in C4-C8) and 96.4 ppm (C6 in C4-C6) (Balde et al 1991b;Balde et al 1995;Navarette et al 2010). Judging by a diagnostic feature peak at 100.1 ppm related to ketal carbon signal (C2 in A-type procyanidins), condensed tannins of grey alder also contain double bond flavanyl units in the molecule (2C-O-7C), which is typical for A-type procyanidins (Lin and Lee 2010).…”
Section: Figurementioning
confidence: 97%
“…Compounds 12-17 were respectively identified as kaempferol-3-O-b-D-glucopyranoside (Kazuma et al, 2003), kaempferol-3-Ob-D-galattopyranoside (Lin et al, 2011), kaempferol-3-O-b-Darabinopyranoside (De Almeida et al, 1998, nicotiflorin (Kazuma et al, 2003), kaempferol-3-robinobioside (Cardoso et al, 2005) and kaempferol-3-neohesperidoside (Kazuma et al, 2003).…”
Section: Isolation and Determination Of Structurementioning
confidence: 99%